Navigating between two the worlds of school and 'being on the land': Arctic Indigenous young people, structural violence, cultural continuity and selfhood. (7th February 2022) - Salusky, Ida R.; Kral, Michael; Amarok, Barbara; Wexler, Lisa M.
ABSTRACT: This qualitative study examines two contexts shaping circumpolar Indigenous young people's contemporary lives. In Arctic North America, the recent, rapid experiences of colonization are linked to disproportionately high rates of youth suicide. It is important to understand how different contexts, central to identity narratives, enhance or challenge resilience: the negotiated capacity to overcome hardship. We examine two settings: school and the land using thematic analysis. School settings occupy significant time in the lives of Indigenous youth from which parents and Indigenous traditions are largely removed. In contrast, the deepening of relationships, spiritual grounding and traditional practices in which Indigenous families engage on the land, signify and amplify cultural and family strengths. Using youth narratives about their lives, we contrast these two settings and the ways they influence young people's wellness through their perceptions of themselves and society. We recommend how schools can better support strengths of Indigenous cultures, including close relationships with family and the land.